A Convenient and General Reduction of Amides to Amines with Low‐Valent Titanium. Issue 14 (2nd October 2013) - Zhang, Tongxin; Zhang, Yan; Zhang, Weixi; Luo, Meiming
Abstract Low‐valent titanium readily prepared in situ from TiCl4 and Mg powder in THF is found to be an active agent for the reduction of amides which were previously considered to be inert towards low‐valent titanium. The reaction proceeds under very mild conditions, and is applicable to all types of amides, primary, secondary and tertiary, to produce the corresponding amines in good to excellent yields. This new finding provides a practical, convenient and general method for the important transformation of amides to amines. A plausible reaction mechanism is proposed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>